2018
DOI: 10.21272/sec.2(4).80-86.2018
|View full text |Cite
|
Sign up to set email alerts
|

Tourism In Developing Countries. The Path Towards Sustainable Development And Its Interaction With The Local Communities, The Environment And The Human Factor

Abstract: This paper summarizes the arguments and counterarguments within the scientific discussion on the issue of tourism in developing countries. The main purpose of this literary analysis is to underline the importance and to shed some light on how government's policies, environmental issues, corporate social responsibility and growth strategies impact in tourism development in developing countries. Also, the paper tries to explain in which way tourism development in such countries impacts in their poor local popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Therefore, countries have incorporated tourism into their long-term economic development planning systems. Although the link between the economic growth and tourism development is obvious, Karaoulanis (2018) emphasizes that tourism development is a product of economic growth and not the other way round.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, countries have incorporated tourism into their long-term economic development planning systems. Although the link between the economic growth and tourism development is obvious, Karaoulanis (2018) emphasizes that tourism development is a product of economic growth and not the other way round.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, enhancing sustainable tourism was related to the tourists' green awareness. In addition, the authors of [29][30][31][32], who investigated the Caribbean Region, Greece, and Armenia using questionnaires and statistical analysis, confirmed that social capital and the level of green awareness in a society influence sustainable tourism development.…”
Section: Literature Reviewmentioning
confidence: 87%
“…Such facilities include material residues of production, industrial landscape, product residues, documentation, and social infrastructure of enterprises. Many sources emphasize that this type of tourism is an effective way to restructure a particular region together with its directions such as health and green or ecotourism (Karaoulanis & Vasiliki, 2018;Tovmasyan & Tovmasyan, 2020;Letunovska et al, 2020). Significant changes in the structure of production that have taken place in various European countries in recent years create a prerequisite for the emergence and development of industrial tourism.…”
Section: Introductionmentioning
confidence: 99%